THE BASE OF KNOWLEDGE FOR THE PHYSICAL EDUCTION TEACHING: THE VIEW OF TEACHERS EDUCATOR (Fiep Bulletin - online, 2014)
This article integrates a set of questions and analysis about the PhD research in process. The issue is about reforming the teacher's education curriculum within the Physical Education course at State University of Londrina /UEL. The process of reforming the curriculum established for every graduation course at National institutions of Higher Education which is made by the National Curriculum Guideline - CP01, CP02 in 2002 - supported these modifications. Considering the course of Physical Education at UEL as a reference for these modifications, we can realize that the curriculum project of this course was installed in 2005 and it´s treating specifically the Physical Education teacher's education to work in different levels and modalities of teaching. Considering Brazilian education historical differences between the Physical Education Graduation course and other graduation courses - and also considering the curriculum's implantation of Physical Education Teachers' Formation, we made the following questions: What´s the base of knowledge for the Physical Education Teachers' Education? The aim view identifying and analyzing that knowledge is considered as an important matter for the Physical Education teachers' education, under a perspective of the teachers involved in the curriculum mentioned above. Eleven (11) teachers were interviewed. There were different subject teachers and different studies area teachers who worked in the first year of the course (2005). The reports of these teachers were obtained by an analyzed and semi-structured interview that started from the construction of the Thematic Analysis Unit. We can say that the results show emphasis in the knowledge of a specific matter as necessary for the Physical Education teachers' education and also show emphasis in theoretical lack of meaning of the basic knowledge for the Education.
Keywords: Teachers' formation; Curriculum; Physical Education